1992
DOI: 10.1161/01.atv.12.9.1030
|View full text |Cite
|
Sign up to set email alerts
|

Influence of insulin resistance, secretion, and clearance on serum cholesterol, triglycerides, lipoprotein cholesterol, and blood pressure in healthy men.

Abstract: Relations between serum lipids, lipoproteins, blood pressure, and insulin metabolism were investigated in 158 healthy men aged 19-77 years and with body mass indexes (BMIs) of 19-41 kg • m" 2 . Mathematical modeling analysis of glucose, insulin, and C-peptide concentrations during an intravenous glucose tolerance test was used to measure parameters of insulin metabolism. In univariate analysis, both fasting and postglucose insulin concentrations showed significant positive associations with fasting serum trigl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
3

Year Published

1994
1994
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 45 publications
3
16
3
Order By: Relevance
“…Blades et al [45] have reported that a high hepatic li-pase activity is associated with low HDL but normal VLDL levels. In addition, there is evidence to suggest that insulin resistance may influence the activity of both lipoprotein and hepatic lipase enzymes [46,47]. In support of this, we have observed a decrease in lipoprotein lipase/hepatic lipase ratio in insulin-resistant males [48].…”
Section: Discussionsupporting
confidence: 76%
“…Blades et al [45] have reported that a high hepatic li-pase activity is associated with low HDL but normal VLDL levels. In addition, there is evidence to suggest that insulin resistance may influence the activity of both lipoprotein and hepatic lipase enzymes [46,47]. In support of this, we have observed a decrease in lipoprotein lipase/hepatic lipase ratio in insulin-resistant males [48].…”
Section: Discussionsupporting
confidence: 76%
“…27,28 Although the positive association between IR and a high BP has been reported to be independent of obesity in some studies, 26,29 other studies have suggested that obesity, in particular central obesity, may be the cause of this association. 24,28,30,31 However, the present study showed that the level of IR, BMI and waist circumference were independent risk factors of a high BP in normoglycemic Koreans.…”
Section: Discussioncontrasting
confidence: 62%
“…A relatively weak univariate correlation between insulin-related variables and HDL cholesterol was also seen in an analysis of data acquired more recently during the course of the HDDRISC study. 3 However, this data also included measurement of HDL 2 subfraction cholesterol, which showed a stronger correlation with insulin-related variables than did total HDL cholesterol. It is therefore possible that factor associations between HDL-and insulin-related measures might have been apparent in the HDDRISC-1 participants had HDL 2 subfraction measurements been available.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] It has been proposed that such intercorrelations indicate a distinct metabolic syndrome in which insulin resistance may have a central role. [6][7][8] Such a syndrome could include impaired glucose tolerance, hyperinsulinemia, high blood pressure, hypertriglyceridemia and low HDL concentrations, increased levels of the antifibrinolytic factor plasminogen activator inhibitor-1, increased levels of the atherogenic small, dense LDL, hyperuricemia, postprandial hyperlipidemia, and central obesity.…”
mentioning
confidence: 99%